Multimodal neuroimaging as a window into the pathological physiology of schizophrenia: Current trends and issues. (January 2016) - Isobe, Masanori; Miyata, Jun; Hazama, Masaaki; Fukuyama, Hidenao; Murai, Toshiya; Takahashi, Hidehiko
Highlights: Hypotheses of schizophrenia are re-examined with multimodal neuroimaging methods. Further multimodal neuroimaging studies are required to conclude hypotheses. Social cognitive impairments may be based on different neural abnormalities. Coupled mechanism between gray and white matter abnormalities is suggested. Abstract: Visualizing the detailed brain anatomy of individuals with schizophrenia has been made possible by recent advances in magnetic resonance imaging (MRI). Although structural MRI cannot be currently used to diagnose schizophrenia, multimodal MRI can reveal insightful information on key clinical aspects of the pathological physiology of schizophrenia. However, in this regard, the number of multimodal MRI studies is still limited and definitely required. In this review, we discuss how classical and popular theories on the pathological physiology of schizophrenia can be re-examined using neuroimaging studies, and also discuss how multimodal MRI studies may provide additional findings. The pathological hypotheses examined include the "progressive brain disease hypothesis" and "disconnection hypothesis". This article is discussed mainly based on recent findings published by our research group.